Sapta Pesona Grouse Island Attractions: Cape of Good Hope District of Solok - Maryeti, Evi; Bakaruddin, Bakaruddin; Suarto, Edi (Pendidikan Geografi, 2013)
This study aims to obtain data or information, discuss and analyze the application of the Sapta charm ( 1 ) security, ( 2 ) Order, ( 3 ) cleanliness, ( 4 ) Coolness, ( 5 ) beauty, ( 6 ) hospitality, ( 7 ) Memories Grouse Island attractions Solok District of Cape of Good Hope .The research is qualitative research that aims to understand the phenomenon of research subjects. Retrieval techniques informants by purposive sampling (designation), in which the subject of research is the study, tourism office , Supervisor / manager, the village chief, Community and visitor attractions Grouse Island . When the study was conducted from July 16 until August 16, 2013. Data was collected through observation, interviews, and documentation .Research results in the field as follows : security and order can grouse island attraction orderly and well controlled, hygiene is quite clean, coolness, beauty, and hospitality is very beautiful and kind, while the charm of memories is still lacking and there has been no implementation.